The Effect of Social Media Application-Based Interventions on HIV Adherence to ARV Medication among Patients with HIV - Herawati, Eva; Nursanti, Irna; Irawati, Diana; Natashia, Dhea; Damayanti, Sri Utami (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: The purpose of this study was to determine the effect of health interventions based on social media applications on HIV patients' adherence to taking ARV medication.  Method: In this study, 76 were selected using a quasi-experimental methodology and a purposive sampling technique. then divided into two distinct groups: intervention and control. During the study, respondents in the intervention group received treatment in the form of reminders via WhatsApp and the SiARV web application. The control group was only given standard health services without any technology-based health interventions. Results: Significant changes in treatment adherence were observed in both the intervention group (p=0.001) and the control group (p=0.001). The difference in treatment adherence between the intervention group and the control group was statistically significant (p=0.040). In the context of multivariate analysis, education was found to be predictive of changes in respondent Adherence (p = 0.019; OR = 3.692). Discussion: Awareness of ARV adherence can be increased and maintained through SiARV social media as a strategy for reminding and controlling patient adherence Conclusion: HIV patients' adherence to taking ARV medications is affected by health interventions utilizing social media applications. It is anticipated that providing HIV patients with application-based interventions and a high level of patient knowledge through education will enhance their quality of life.